THE IMPACT OF EMPLOYEE TRAINING ON AUDITOR’S PERCEPTION OF AUDIT RISK - Angelina Oktavia Ramadani (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
This study investigates the impact of employee training on auditors’ perceptions of audit risk within Indonesian public accounting firms. Using a quantitative approach, data were collected from 200 auditors through structured surveys, focusing on demographic characteristics, training experiences, and perceptions of audit risk. Descriptive and regression analyses reveal that training significantly influences auditors’ confidence and ability to assess risks. Approximately 75% of respondents who participated in formal training reported enhanced capability in identifying audit risks, underscoring the value of continuous professional development. The results also indicate that training effectiveness is shaped by type, frequency, and organizational support. Practice-based and case-oriented training produced stronger effects than theoretical instruction, while auditors receiving annual training demonstrated a 30% higher improvement in risk perception compared to those trained biennially. Managerial support was further identified as a critical factor in encouraging proactive risk identification. The findings reinforce learning theory, confirming that knowledge and skills gained through training enhance professional judgment and audit quality. Theoretically, this study expands audit literature by demonstrating the importance of training as a determinant of risk perception, while practically it highlights the need for structured, sustainable, and case-based training programs with strong managerial involvement. Despite limitations related to sample scope and quantitative design, the study provides important insights for advancing auditor training policies and strengthening audit quality.